The Influence of Brand, Attitude, and Brand Knowledge on Purchase Intention and Its Impact on Purchase Decisions for Organic Food Products in Banda Aceh (International Journal of Scientific Research and Management (IJSRM), 2025)
This research aims toto test the influence of brand, attitude, and brand knowledge on purchase intention and its impact on purchasing decisions of organic food products in Banda Aceh.In this study the population isall Consumers of Organic Food Products in Banda Aceh.The research sample was 200 people. The analysis method used was Partial Least Square (PLS).The results of the study showed thata brand has a positive effect on Purchase Intention, attitude has a positive effect on Purchase Intention, brand knowledge has a positive effect on Purchase Intention, brand has a positive effect on purchase decision, attitude has a positive effect on purchase decision, brand knowledge has a positive effect on purchase decision, and Purchase Intention has a positive effect on purchase decision. Furthermore, for mediation testing, Purchase Intention partially mediates the influence of brand, attitude, and brand knowledge on purchasing decision of Organic Food Products in Banda Aceh